MODIFIKASI MESIN MOTOR RODA DUASERI BEAT ESP 2017 HEMAT ENERGI DENGAN METODE STROKE UP DAN BORE UP - Kholis Nur Faizin; Achmad Aminudin (JURNAL INTEGRASI, 2019)
This research is motivated by the depletion of fuel oil supplies in Indonesia, while the needs of the public are increasingly reminded. This energy also cannot be updated. It takes thousands or even millions of years of the time needed by nature to form the fuel oil. One of its efforts is to reduce fuel consumption. The compiler effort in supporting the savings program is to modify the vehicle. The research objective of this is to find out how to modify the engine to be more fuel efficient and know how to make noise levels not more than 90 dB. This study uses the method of stroke up, bore up and low profile camshaft, so the engine character becomes overstroke. Overstroke means the stroke distance is longer than the bore. This vehicle will produce the advantages of fast starting and large and strong torsion and the use of fuel can be minimized. This research is expected to be able to optimize combustion in the combustion chamber so as to reduce fuel consumption and noise.